Lek phenology of the White-bearded Manakin (Manacus manacus, Aves: Passeriformes: Pipridae) in a subtropical region - Cestari, Cesar [UNESP]; Pizo, Marco Aurelio [UNESP] (Taylor & Francis Ltd, 2012)
Descriptions of lek-breeding in White-bearded Manakins (Manacus manacus) first appeared 55 years ago from studies conducted in tropical Trinidad. No published studies on lek activity, however, exist from subtropical areas of the Neotropics. Herein, annual lek phenology of M. manacus in a subtropical region was analysed and compared with studies conducted in Trinidad. Day-long observations were conducted in nine male territories from three leks. Permanence of lekking males in their territories was positively correlated with day length. When males are more active in the subtropical region, males from Trinidad are less active and vice versa. Additional new information about this manakin's lek activity was disclosed: residents stayed in their courts for up to 7% of the day length, the frequency and duration of display bouts of residents varied throughout the year whereas those of juveniles did not, and females made more visits to courts of residents who displayed for longer bouts.
Keywords: behaviour; day length; manakins; sexual selection; southeastern Brazil; temporal analysis